Mathematics Asked on January 5, 2022

I was looking at the equation $$frac{1}{a}+frac{1}{b} = frac{c}{d},,$$ where $c$ and $d$ are positive integers such that $gcd(c,d) = 1$.

I was trying to find positive integer solutions to this equation for $a, b$, given any $c$ and $d$ that satisfy the above conditions. I was also trying to find whether there are additional requirements on $c$ and $d$ so that positive integer solutions for $a$ and $b$ can even exist.

I found that this equation simplifies to $abc – ad – bd = 0$ so that $abc = d(a+b)$.

Also, since the equation is equivalent to $a+b = ab(frac{c}{d})$, this means $a$ and $b$ are the roots of the quadratic $dx^2-abcx+abd = 0$ since their product is $ab$ and their sum is $a+b = ab(frac{c}{d})$.

However, after I analyzed the quadratic I just ended up with $a = a$ and $b = b$.

Any ideas on how to solve this further?

Again, I need to find all the conditions on the positive integers $c$ and $d$ (where $gcd(c,d) = 1$) such that positive integer solutions for $a, b$ can exist. And then also find the positive integer solutions for $a$ and $b$ given that those conditions are satisfied.

The first equation is equivalent to (ac-d)(bc-d) = d^2. From there, you can find all the ways that two numbers multiply to d^2. If you have two numbers e and f that multiply to be d^2, then you can solve ac-d = e, bc-d = f individually. This stems from Simon's Favorite Factoring Trick that another person mentioned.

Answered by user832828 on January 5, 2022

$frac{1}{a}+frac{1}{b} = frac{c}{d},,$

Above has solution:

$a=(3k-2)$

$b=(k-2)(3k-2)$

$c=(k-1)(3k-2)$

$d=(k-2)(3k-2)^2$

For k=5 we get:

$(a,b,c,d)=(13,39,52,507)$

Answered by Sam on January 5, 2022

Try some examples. I suggest researching Simon's Favorite Factoring trick, it helps with these types of questions. Asking on artofproblemsolving.com is a great idea, Simon is a real person who invented this factoring trick, and it's on that website.

I'll give you one example. Let's take $frac{1}{a}+frac{1}{b}=frac{1}{4}$. Note that $frac{a+b}{ab}=frac{1}{4}$. So, $4a+4b=ab$, meaning that $ab-4a-4b=0$, so $(a-4)(b-4)=16$. To solve this in the integers, just find the factor pairs of $16$ and solve for $a,b$

Hope this helped you!

Answered by OlympusHero on January 5, 2022

Get help from others!

Recent Questions

- How can I transform graph image into a tikzpicture LaTeX code?
- How Do I Get The Ifruit App Off Of Gta 5 / Grand Theft Auto 5
- Iv’e designed a space elevator using a series of lasers. do you know anybody i could submit the designs too that could manufacture the concept and put it to use
- Need help finding a book. Female OP protagonist, magic
- Why is the WWF pending games (“Your turn”) area replaced w/ a column of “Bonus & Reward”gift boxes?

Recent Answers

- Lex on Does Google Analytics track 404 page responses as valid page views?
- Jon Church on Why fry rice before boiling?
- Joshua Engel on Why fry rice before boiling?
- Peter Machado on Why fry rice before boiling?
- haakon.io on Why fry rice before boiling?

© 2024 TransWikia.com. All rights reserved. Sites we Love: PCI Database, UKBizDB, Menu Kuliner, Sharing RPP